REHABILITACJAThe evaluation of exercise capacity and psychological condition in patents with a history of the surgical treatment of congenital heart diseases - Gierat-Haponiuk, Katarzyna; Haponiuk, Ireneusz; Chojnacki, Maciej; Kwiatkowska, Joanna; Zielińska, Dominika; Bakuła, Stanisław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Introduction: Patients with congenital heart defects are a growing population due to the growing quantity of adults after successful surgical treatment in childhood (GUCH – grown-up congenital heart defects). The fear related to the heart disease itself and lower than normal exercise capacity deepen the feeling of the illness and make professional, family and social life more difficult. In order to assess the health state of young GUCH patients, the evaluation of exercise capacity and psychological condition is needed. Aim: The aim of the study was to evaluate the exercise capacity and psychological state in young patents with a history of congenital cardiac surgery. Material and Methods: 20 young patients with a history of the remote (mean: after 19,4 years) surgical treatment of congenital heart diseases were included to the study. Cardiopulmonary exercise testing on bicycle ergometer, Beck depression inventory and inquiry concerning life style were performed in every patient. Results: In young patients after the surgical treatment of congenital heart diseases the lower exercise capacity than in healthy subjcets is observed. All patients expressed the need of taking part in the comprehensive cardiac rehabilitation program. Conclusions: The health status of patients with a remote history of congenital cardiac surgery in the meaning of the exercise capacity seems to be worse than in healthy subjects. The fear of physical activity make their social and occupational life more difficult.